2021
DOI: 10.1101/2021.12.13.21267077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Change in Finances, Peer Access, and Mental Health Among Trans and Non-binary People in Canada During COVID-19

Abstract: Purpose COVID-related stressors associated with loss of income and community are compounded with gender minority stress among trans and non-binary people (TNB), which may result in mental health burden. The present study examined the effect of COVID-related change in finances and TNB gathering access on anxiety and depression among TNB people. Methods Participants were 18 years and older (M age = 30) who completed both pre-pandemic baseline (Fall 2019) and pandemic follow-up (Fall 2020) surveys in the Trans P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(39 reference statements)
1
0
0
Order By: Relevance
“…We found support for the role of family social support in moderating the associations between LGB-POC Microaggressions and depression as well as stress but not with anxiety. The lack of significant moderation of social support in predicting anxiety aligns with recent research (Ghabrial et al, 2021) that found the moderating effects of social support in relation to depression but not with anxiety, perhaps due to the similar reasons described above. In our study, we found that having greater family social support was associated with lower levels of depression (see Figure 1) and stress (see Figure 2) across different levels of intersectional microaggressions.…”
Section: Discussionsupporting
confidence: 88%
“…We found support for the role of family social support in moderating the associations between LGB-POC Microaggressions and depression as well as stress but not with anxiety. The lack of significant moderation of social support in predicting anxiety aligns with recent research (Ghabrial et al, 2021) that found the moderating effects of social support in relation to depression but not with anxiety, perhaps due to the similar reasons described above. In our study, we found that having greater family social support was associated with lower levels of depression (see Figure 1) and stress (see Figure 2) across different levels of intersectional microaggressions.…”
Section: Discussionsupporting
confidence: 88%